Penggunaan Model Pembelajaran Market Place Activity dalam Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran PAI - Dedeh Nurjanah; Titin Karlina; Wiwik Dyah Aryani (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This research was motivated by the problem of teacher difficulties in determining learning models and decreased student learning activity. The purpose of this study is to increase student learning activity through the Market Place Activity learning model. This research is a class-based action research, this research is conducted in two cycles. Each cycle consists of four activities: action planning, observation, and reflection. The subject of this study was students of Class X Pharmaceutical Technology 1 SMK YPF Bandung. Data collection is done through documentation, observation, interviews, field notes, and research instruments. Data analysis is done by reducing data, presenting data, and drawing conclusions. The results of this study show that the MPA learning model can increase the activeness and learning outcomes of class X Information Technology 1 students of SMK YPF Bandung. This learning model can also stimulate students to be actively involved in both physical and non-physical learning (thinking).